PENERAPAN READING GUIDE DENGAN MEDIA BLOG CONTEXTUAL CONTENT DALAM MENINGKATKAN DAYA BERFIKIR KRITIS PADA MAHASISWA IKIP BUDI UTOMO MALANG - Feri Candra Setiawan; Ferdinan Bashofi (IKIP Budi Utomo Malang, 2018)
This research aims to determine the effect of applying learning model of reading guide with blog contextual content media on students majoring in history at IKIP Budi Utomo Malang. The sample in this research is the students of history class 2017 IKIP Budi Utomo Malang.This research is a kind of Quasi experimental design and this research including with pre-test and post-test control group design.The research of African history learning with the model of reading guide with media blog contextual content is stated enough to give effect even in low level. This is indicated by: (1) the students’ critical thinking ability exceeds minimalcompletenesseither individually or classically, (2) the critical thinking skill of students who are given the model of reading guide with contextual content blog media is better than the class given conventional learning, (3) variable Reading Guide sig = 0.087 = 8.7%> 5%, so H0 is accepted, meaning that the reading guide has no influence on the variable of critical thinking ability, but Blog Contextual content variable there is positive influence with index sig = 0,030 = 0% <5% so H0 is rejected, it means Contextual Content Blog has influence to critical thinking ability variable or together between reading guide model and blog contextual content media to critical thinking ability, and (4) improvement of critical thinking ability of students who are given learning model of reading guide with media blog contextual content is better than the class that is given conventional learning.